1975
DOI: 10.1182/blood.v45.3.321.bloodjournal453321
|View full text |Cite
|
Sign up to set email alerts
|

Human chronic myelogenous leukemia cell-line with positive Philadelphia chromosome

Abstract: A cell-line derived from a patient with chronic myelogenous leukemia (CML) is described. The new cell-line, which has over 175 serial passanges in a 3 1/2-yr period, has the following characteristics: (1) CML cells started to proliferate actively since they were first incubated in culture media. A threefold increase in the total number of cells was observed during the first seven passages; the cell population increased by a factor of 10 to 20 every 7 days from passage 8 through 85; from 20 to 40 times from pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
181
1
1

Year Published

1986
1986
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,092 publications
(184 citation statements)
references
References 23 publications
1
181
1
1
Order By: Relevance
“…MEL extract preparation. MEL cells (30) were grown in ␣ minimal essential medium with 10% calf serum and 1ϫ penicillin-streptomycin-L-glutamine and induced with N,NЈ-hexamethylene bisacetamide (HMBA) at 5 mM 36 to 48 h prior to extract preparation. All centrifugation steps were carried out at 4ЊC.…”
Section: Methodsmentioning
confidence: 99%
“…MEL extract preparation. MEL cells (30) were grown in ␣ minimal essential medium with 10% calf serum and 1ϫ penicillin-streptomycin-L-glutamine and induced with N,NЈ-hexamethylene bisacetamide (HMBA) at 5 mM 36 to 48 h prior to extract preparation. All centrifugation steps were carried out at 4ЊC.…”
Section: Methodsmentioning
confidence: 99%
“…Co-expressing AE1 and AE1 SAO in oocytes did not interfere with the trafficking of AE1 to the surface [22], although hetero-oligomerization was not shown in this study. AE1 SAO has also been stably expressed in K562 cells [24], a human erythroleukaemia cell line that expresses GPA [25]. The presence of Wr b epitopes on K562 cells transfected with AE1 SAO demonstrates that AE1 SAO is able to interact with GPA.…”
Section: Figure 1 Folding Model Of Human Ae1mentioning
confidence: 99%
“…We then asked the question whether the minilocus construct would be active in erythroid cells representing a different stage of development or in a non-erythroid cell line. The human cell line K562 (Lozzio and Lozzio, 1975), which expresses the human y-, but not the 8-globin gene, was chosen for the first purpose, since it had been shown previously that transfected y-, but not @globin genes (without flanking regions) can be expressed in these cells (Kioussis et al, 1985;Antoniou et al, 1987;Rutherford and Nienhuis, 1987). Mouse L cells were chosen as a nonerythroid cell, since it has been shown that this cell is capable of expressing transfected 6-globin genes (Dierks et al, 1981;Busslinger et al, 1983;Murray and Grosveld, 1987).…”
Section: Expression In K562 and L Cellsmentioning
confidence: 99%